SOLVENCY OF CURRENT ACCOUNT DEFICITS IN TURKEY - Kayikci, Fazil (NATIONAL ACAD MANAGEMENT, 2012)
Long-run relationship between the export and the import ratios to the GDP for Turkey with quarterly data between 1992 and 2009 is searched by different cointegration tests. There are detected structural breaks in the second quarter of 1998 for the imports and in the first quarter of 2001 fir the exports. Even though exports and imports have a long-run relationship and more together with structural breaks, the exports seem to compensate 69% of the imports until the break in the third quarter of 2000 whereas it only compensates 54.4% after 2000. This means that the path of unsustainable foreign trade became more dangerous after 2000.
Keywords: current account; balance of payments; solvency; cointegration; UNIT-ROOT HYPOTHESIS; OIL-PRICE SHOCK; GREAT CRASH; PANEL-DATA; SUSTAINABILITY; PRODUCTIVITY; TOO; Business & Economics